2019
DOI: 10.1038/s41557-019-0342-6
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable-battery chemistry based on lithium oxide growth through nitrate anion redox

Abstract: Next-generation lithium-battery cathodes often involve the growth of lithium-rich phases, which enables specific capacities that 2-3 times higher than insertion cathode materials such as lithium cobalt oxide (LiCoO 2). Here, we investigate battery chemistry previously deemed irreversible in which lithium oxide (Li 2 O), a lithium-rich phase, grows through reduction of the nitrate anion in a lithium nitrate-based molten salt at 150 °C. Using a suite of independent characterization techniques, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
1
33
1
Order By: Relevance
“…It is commonly assumed that the beneficial effects of LiNO 3 come mostly from its role in regulating chemistry and transport properties of interphases formed on the Li electrode. Various literature has also explained the beneficial effects of LiNO 3 in terms of its influence on Li surface chemistry and solvation of intermediates formed at Li electrodes in liquid electrolytes (14,29,(36)(37)(38). Because Li already exhibits exceptional reversibility in the DOL electrolyte, we hypothesized that these electrolytes would provide a good testbed for understanding how LiNO 3 works.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly assumed that the beneficial effects of LiNO 3 come mostly from its role in regulating chemistry and transport properties of interphases formed on the Li electrode. Various literature has also explained the beneficial effects of LiNO 3 in terms of its influence on Li surface chemistry and solvation of intermediates formed at Li electrodes in liquid electrolytes (14,29,(36)(37)(38). Because Li already exhibits exceptional reversibility in the DOL electrolyte, we hypothesized that these electrolytes would provide a good testbed for understanding how LiNO 3 works.…”
Section: Resultsmentioning
confidence: 99%
“…They typically form as part of a solidelectrolyte interphase (SEI) passivation layer when a low-voltage anode reduces an electrolyte that contains the elements oxygen or sulfur. [1][2][3] They are also an important reaction product in conversion electrodes based on oxides, 4 oxygen, 5 nitrates, 6 sulfides, 4 sulfur, 7 and so on. The solid-state ion transport rates within the Li 2 O and Li 2 S can limit battery performance, yet the rates are not well-understood, partly because many phases are involved.…”
mentioning
confidence: 99%
“…Prior studies in primary thermal batteries have reported NO 3 – → NO 2 – nitrate to nitrite reduction driven by catalytic electrodes. , Using Ni nanoparticles as catalytic cathodes, Giordani et al. have demonstrated a rechargeable electrochemistry with the main deposition product as Li 2 O. The grand potential analysis currently does not capture the NO 3 – → NO 2 – nitrate to nitrite reduction.…”
Section: Resultsmentioning
confidence: 99%